Research on Performance Analysis and Optimal Design of Bearing-rotor System of Ultra-high Speed Gearbox - Junhao Chen; Chunbo Liu; Linjie Yang; Luji Wu (Jixie chuandong, 2021)
Based on the tilting pad bearing rotor system， the influence of bearing span，shaft diameter and bearing related parameters on the critical speed of bearing-rotor system is analyzed through simulation calculation， which provides the basis for the optimal design of high-speed gearbox bearing-rotor system. The influence of the span is closely related to the speed， when the shaft diameter exceeds 54 mm， the influence is negligible， the clearance ratio， pivot offset and preload coefficient have basically the same influence on the first and second order critical speeds. The relationship curves are linear，logarithmic and exponential. According to the analysis results，the gearbox of 60 000 r/min is designed，the bearing-rotor system passed the no-load test，and the overall performance of the gearbox met the requirements.